Stroke Chameleon: Acute Bilateral Middle Cerebral Artery Infarct Complicated with Acute Pulmonary Oedema - Baharuddin, Kamarul Aryffin; Wanshah, Nurlina; Abdul Halim, Sanihah; Ghazali, Fattah Rahiman (IIUM Medical Journal Malaysia, 2025)
Acute bilateral middle cerebral artery (MCA) infarctions are an extremely rare event. However, it can cause disruption of bilateral corticothalamic networks leading to coma. Detection of this condition is challenging as the early ischemic signs found on the non-contrast CT (NCCT) is depending on comparison between infarcted region and its normal counterpart. We report a case of 60-year-old man presented with acute comatose state and pulmonary oedema secondary to hypertensive emergency. His NCCT brain showed acute infarction of bilateral MCA territories. His acute pulmonary oedema subsequently resolved with the treatment. However, he succumbed to his illness and its complications on day 7 of admission. In this case report, we explore the strategy to improve detection of bilateral infarction on NCCT and navigating the differential diagnosis of comatose state and acute pulmonary oedema brought about by the hypertensive emergency.